Straighten the given line into a functional form.

5X - 7Y = 6

- 7Y = - 5X + 6

Y = 5/7X - 6/7

====== slope is 5/7

so, use point slope form and the slope found with points given (6, - 6)

Y - Y1 = m(X - X1)

Y - (- 6) = 5/7(X - 6)

Y + 6 = 5/7X - 30/7 ( 6 = 42/7 )

Y = 5/7X - 72/7

------( your equation ) I am too lazy to check, so my TI-84 will!!

These line are parallel.

5X - 7Y = 6

- 7Y = - 5X + 6

Y = 5/7X - 6/7

====== slope is 5/7

so, use point slope form and the slope found with points given (6, - 6)

Y - Y1 = m(X - X1)

Y - (- 6) = 5/7(X - 6)

Y + 6 = 5/7X - 30/7 ( 6 = 42/7 )

Y = 5/7X - 72/7

------( your equation ) I am too lazy to check, so my TI-84 will!!

These line are parallel.